2015
DOI: 10.3402/fnr.v59.28610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of goat milk–based formula on development in weaned rats

Abstract: ObjectiveThe aim of this article is to study the effect of goat milk–based formula (GMF) on development in weaned rats.MethodsOne hundred Sprague-Dawley rats were randomly divided into five groups: control, 20% cow milk–based formula (CMF), and 5%-GMF, 10%-GMF, and 20%-GMF groups.ResultsGMF did play an active role in accelerating body and femur length, but not body weight growth. Compared with the control, GMF had better cognitive, space, and locomotor activity. The level of IFN was increased in GMF groups, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
10
0
4
Order By: Relevance
“…This was explained by the fact protein needed to avoid weight loss in rats fed the protein-free diet is equal to the protein necessary for maintenance (Sarwar, 1997). These results were in agreement with those obtained by (Grant et al, 2005;Rutherfurd et al, 2006;Xu et al, 2015b;Zhou et al, 2014).…”
supporting
confidence: 87%
“…This was explained by the fact protein needed to avoid weight loss in rats fed the protein-free diet is equal to the protein necessary for maintenance (Sarwar, 1997). These results were in agreement with those obtained by (Grant et al, 2005;Rutherfurd et al, 2006;Xu et al, 2015b;Zhou et al, 2014).…”
supporting
confidence: 87%
“…Goat milk contains smaller fat globules and larger amounts of short- and medium-chain fatty acids than cow milk. These increase the digestibility and bioavailability of goat milk ( Park, 1994 ; Xu et al ., 2015 ). Goat milk also contains abundant vitamins (A, E, B 1 , B 2 , and C) and minerals (potassium, calcium, magnesium, phosphorus, sodium, iron, copper, and zinc) with a superior absorption rate ( Kim et al ., 2013 ; Kim et al ., 2015 ; Rutherfurd et al ., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the memory performance of the D-gal rats treated with goat milk was comparable to that of the normal control rats, suggesting that goat milk has the ability to normalize memory functions. Xu et al (2015) reported that goat milk based formula resulted in superior cognitive and spatial ability in weaned Sprague Dawley rats, as compared to control rats and also as compared to rats supplemented with cow milk based formula 9 . Medeiros et al (2018) made use of goat whey, which is a by-product of cheese curd production from goat milk, to test memory performance in moderately malnourished male pups; they reported that goat whey was able to enhance memory performance in those pups when compared with the pups in the control group 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Goat milk has high nutritional value and plays a vital role in human nutrition. It is known to contain proteins, vitamins, and fatty acids that possess immense biological merit 8,9 . Goat milk possesses higher levels of calcium, potassium and phosphorus-compared to both human and cow milk-and a substantially higher protein concentration compared to human milk 10,11 .…”
Section: Introductionmentioning
confidence: 99%